CSIG-04. PAN-RTK INHIBITION OF sLRIG1 MEDIATES AXL DOWNREGULATION IN GLIOBLASTOMA. (11th November 2019) - Neirinckx, Virginie; Hau, Ann-Christin; Schuster, Anne; Fritah, Sabrina; Chevigné, Andy; Schmidt, Mirko H; Niclou, Simone
Abstract: INTRODUCTION: Aberrant regulation of receptor tyrosine kinase (RTK) activity is characteristic of Glioblastoma (GBM). However, RTK-based targeted therapies have been largely unsuccessful in GBM patients, partially due to the complexity and redundance of RTK signaling. LRIG1 (Leucine-rich Repeats and ImmunoGlobulin-like domains 1) is an important endogenous inhibitor of epidermal growth factor receptor (EGFR) during health and disease, however its mechanism of action is poorly understood. We previously showed that the soluble form of LRIG1 potently inhibits GBM growth in vivo, irrespective of EGFR expression level and status, suggesting the involvement of other RTKs. Here, we aimed to shed light on the molecular mechanisms underlying its anti-cancer activity. MATERIAL AND METHODS: We generated a recombinant human soluble LRIG1 protein (rh-sLRIG1) by expressing LRIG1 ectodomain in insect cells via baculovirus infection and subsequent His-tag purification. rh-sLRIG1 was used to treat patient-derived GBM stem-like cells, classical GBM cell lines and patient-derived 3D tumor organoids. Using different cell-based assays, cell proliferation, invasion, cell morphology, as well as protein expression and protein-protein interactions were investigated. RESULTS: We find that recombinant sLRIG1 efficiently reduced proliferation, invasion and viability of GBM cells and patient-derived organoids, and modulated cytoskeleton proteins and cell shape. In line with previous data, the effect of recombinant sLRIG1 was independent of EGFR expression. Interestingly sLRIG1 impacted multiple RTKs including AXL, by direct protein downregulation, while EGFR expression was not affected. At the molecular level, we find that sLRIG1 interfereed with AXL dimerization, while no protein interaction with EGFR was detected. CONCLUSION: We identify AXL as a novel LRIG1 target and provide evidence that sLRIG1-mediated RTK downregulation requires direct protein-protein interaction. These data pave the way for a potential therapeutic application of recombinant sLRIG1 in the inhibition of growth factor signaling in GBM.